Intrinsic over extrinsic: Species identity shapes spatial and interannual Mg/Ca patterns in Arctic marine calcifiers - Małgorzata Krzemińska; Emma Humphreys-Williams; Tomasz Krzykawski; Piotr Kukliński (PLoS ONE, 2026)
Marine calcifiers incorporate magnesium into their calcium carbonate skeletons through processes influenced by both ambient environmental conditions and species-specific physiological regulation. As a result, their carbonate structures can serve as valuable archives of past and present oceanic conditions, provided that biological controls are explicitly considered. This study investigated how skeletal magnesium-to-calcium (Mg/Ca) ratios vary in space and time among three Arctic benthic invertebrates differing in phylogeny, evolutionary history, and biomineralization strategy: the barnacle Semibalanus balanoides , the spirorbid Paradexiospira violacea , and the bryozoan Harmeria scutulata . Mg/Ca ratios were quantified using inductively coupled plasma atomic emission spectroscopy (ICP-AES) across three Svalbard fjords and over a four-year temporal interval (2006–2009). Kruskal–Wallis analyses revealed that species identity was the dominant factor controlling Mg/Ca ratios among the studied taxa. S. balanoides exhibited the lowest values of mean Mg/Ca ratios but highly variable (mean = 35.2 mmol/mol ± 16.8 SD), whereas P. violacea (62.5 mmol/mol ± 14.3) and H. scutulata (65.3 mmol/mol ± 14.1) showed higher and more consistent Mg/Ca ratio. Significant differences in Mg/Ca ratios were observed among sites for all species, following a consistent Hornsund < Kongsfjorden < Isfjorden pattern. However, the magnitude of site-level variability in Mg/Ca differed among species, confirming that species-specific physiological controls exert a stronger influence on skeletal Mg incorporation than external, site-specific environmental conditions. In Isfjorden, interannual trends in Mg/Ca between 2006 and 2009 were found to be species-specific but non-significant for all species. Weak, negative, and statistically significant relationships with bottom-water temperatures in Isfjorden was found only in P. violacea. Overall, these results highlight the predominant role of intrinsic biological controls over ambient environmental conditions in shaping skeletal Mg/Ca ratios and underscore the importance of species-resolved approaches when applying geochemical proxies in rapidly changing Arctic ecosystems.